Networks and selection in international migration to Spain - Nina Neubecker; Marcel Smolka; Anne Steinbacher (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
This paper analyzes the role of ethnic communities in shaping the recent immigration boom to Spain. We find that ethnic communities exerted a strong positive effect on the scale and a strong negative effect on the skill structure of this immigration. Unlike previous studies, we explicitly acknowledge similarities among final migration destinations and thus partly relax the independence of irrelevant alternatives assumption. We strengthen our causal interpretation by controlling for observed and unobserved heterogeneity in bilateral migration costs, and by adopting an instrumental variables approach. Our results suggest that previous estimates of the scale effect are upward-biased by approximately 50%.
urn:nbn:de:bsz:21-opus-62363
Keywords: F22; 330; International migration; Ethnic networks; Family and friends effect; Skill structure of migration; Spain; Einwanderung; Migranten; Ethnische Gruppe; Soziales Netzwerk; Qualifikation; Spanien